PEIRCE’S CONTRIBUTION FOR COMMUNICATION THEORY - Romanini, Vinicius (2016)
Charles Sanders Peirce (1839-1914) made important contributions to Philosophy, Mathematics and Logic. But it was mainly to the latter that most of his studies turned. His general theory of signs, or semiotics, was developed as an attempt to discover the logic that underlies our conceptions of the real and how knowledge grows from confronting and sharing opinions within a community. So, pragmatism – his greatest legacy to Philosophy – was defined by him as a method to clean up our ideas from the analysis of the possible effects that the adoption of a concept (a belief) could produce. From 1905 on, Peirce came to regard the sign as the medium for the transmission of forms that ground the concepts, and communication as the most important of the various types of sign actions. In semiosis, the symbols remain fallible and constantly changing because that is their nature: to grow and develop in a universe that is intelligible and filled with meaning. In this semiotic realism, based on a social theory of knowledge, aesthetics bases ethics, and these both provide the basis for the logic - now understood as a general theory of communication.